On the asymptotic equilibrium and asymptotic equivalence of differential equations in Banach spaces - Nguyen Sinh Bay; Nguyen The Hoan; Nguyen Minh Man (Український математичний журнал, 2008)
We present some conditions for the asymptotic equilibrium of nonlinear differential equations in Banach
spaces, in particular, of the linear nonhomogenous equation. We also discuss analogous problems for the
linear equation with a nonbounded operator. Some obtained results are applied to problems of
asymptotic equivalence. Наведено деякі умови асимптотичної рівноваги нелінійних диференціальних рівнянь у банахо-вих просторах і, зокрема, лінійного неоднорідного рівняння. Також розглянуто аналогічні питання для лінійного рівняння із необмеженим оператором. Деякі отримані результати застосовано до задач асимптотичної еквівалентності.